The Use of Puzzle Media to Improve Concentration and Accuracy Skills of Elementary School Students - Lucia Yasinta; Hendrikus Rahangmetan; Umar Yampap; Rudolfus Ruma Bay (Research, Training and Philanthropy Institution Natural Aceh, 2026)
The objective of this study is to determine the improvement of students' concentration and accuracy through the use of puzzle media. The method used is classroom action Research, which consists of planning, implementation, observation, and reflection cycles. This Research was conducted at SD, located at Jl. Trans Papua, Mandekman, Ulilin, Merauke, South Papua 99635. The study subjects were 28 third-grade students. Data collection included observations of teacher activities, student activities, students' concentration, and students' accuracy. The data analysis techniques measured were: (1) teacher activity data, (2) student activity data, (3) concentration data, and (4) student accuracy data. The study found that using puzzle media improved students' concentration and accuracy in the second cycle, with a score of 77.90 in the good category. Therefore, the use of puzzle media can be considered effective in enhancing elementary school students' concentration and accuracy. The implications of this study are that puzzle media can be used as a learning strategy to help students focus their attention for longer periods, be more careful in matching puzzle pieces, and interact with them in ways that are gradually, attractively, and concretely attractive, thereby creating a pleasant and non-monotonous learning environment.